Premature Deindustrialization and the Defeminization of Labor. Issue 2 (3rd April 2017) - Greenstein, Joshua; Anderson, Bret
Abstract: There is growing evidence of two related global processes happening. The late industrializers are deindustrializing at earlier stages of development than their predecessors, and the global trends in the gender composition of manufacturing and industrial employment are evolving. What is less well known is how these two trends are related to one another. Starting from the premise that industrial upgrading has been observed to have a male bias, we test the hypothesis that premature deindustrialization is likely to amplify that bias. For the empirical test and simulation, we use an economy's global competitive position as a proxy for the deindustrialization regime type. To get to this position, we bring together the work of Nicholas Kaldor, feminist scholarship, and structuralist critiques. The results for sixty-two countries, spanning the years from 1990 to 2013, support our hypothesis that premature deindustrialization is likely to amplify the male bias of industrial upgrading.